Potential of a Pharmacogenetic-Guided Algorithm to Predict Optimal Warfarin Dosing in a High-Risk Hispanic Patient - Dagmar F. Hernandez-Suarez MD; Karla Claudio-Campos BSc; Javier E. Mirabal-Arroyo MD; Bianca A. Torres-Hernández PhD; Angel López-Candales MD, FACC, FASE; Kyle Melin PharmD; Jorge Duconge PhD, BScPharm (SAGE Publishing, 2016)
Deep abdominal vein thrombosis is extremely rare among thrombotic events secondary to the use of contraceptives. A case to illustrate the clinical utility of ethno-specific pharmacogenetic testing in warfarin management of a Hispanic patient is reported. A 37-year-old Hispanic Puerto Rican, non-gravid female with past medical history of abnormal uterine bleeding on hormonal contraceptive therapy was evaluated for abdominal pain. Physical exam was remarkable for unspecific diffuse abdominal tenderness, and general initial laboratory results-including coagulation parameters-were unremarkable. A contrast-enhanced computed tomography showed a massive thrombosis of the main portal, splenic, and superior mesenteric veins. On admission the patient was started on oral anticoagulation therapy with warfarin at 5 mg/day and low-molecular-weight heparin. The prediction of an effective warfarin dose of 7.5 mg/day, estimated by using a recently developed pharmacogenetic-guided algorithm for Caribbean Hispanics, coincided with the actual patient's warfarin dose to reach the international normalized ratio target. We speculate that the slow rise in patient's international normalized ratio observed on the initiation of warfarin therapy, the resulting high risk for thromboembolic events, and the required warfarin dose of 7.5 mg/day are attributable in some part to the presence of the NQO1 *2 (g.559C>T, p.P187S) polymorphism, which seems to be significantly associated with resistance to warfarin in Hispanics. By adding genotyping results of this novel variant, the predictive model can inform clinicians better about the optimal warfarin dose in Caribbean Hispanics. The results highlight the potential for pharmacogenetic testing of warfarin to improve patient care.